Homeopathic management of carbuncle: A case report - Reddy, Mallesh; Kadapa, Lokesh; Tiwari, Asmita (Indian Journal of Case Reports, 2026)
A carbuncle is a deep bacterial infection involving adjacent hair follicles and surrounding subcutaneous tissue,commonly managed with incision and drainage along with antibiotic therapy. A 52-year-old male presented with apainful swelling over the nape of the neck of 5 days’ duration, associated with foul-smelling purulent discharge mixed with blood and pain aggravated at night. The patient was a known case of type 2 diabetes mellitus and hypertension and was on regular allopathic medication. Clinical examination revealed an indurated, tender swelling with purulent discharge and localized inflammation, leading to the diagnosis of a carbuncle. Individualized homeopathic treatment with Tarentula cubensis was prescribed along with local dressing using Calendula officinalis mother tincture. Progressive reduction in pain, discharge, and swelling was observed during follow-up, with complete healing achieved within 1 month without surgical intervention. This case highlights the possible role of individualized homeopathic medicine as a therapeutic approach in carbuncle in a diabetic without recourse to antibiotics or surgical intervention.